Comparison of soil particle density determined by a gas pycnometer using helium, nitrogen, and air. Issue 1 (15th November 2022) - Amoozegar, Aziz; Heitman, Joshua L.; Kranz, Christina N.
Abstract: Soil particle density (ρs ) is often assumed as 2.65 g cm −3 (density of quartz). The objectives of this study were to compare the use of different gases for determining ρs in a gas pycnometer and relate measured ρs to soil particle size distributions. The ρs of 36 natural soil samples representing 12 USDA textural classes, fine glass beads, crushed granite rock, kaolinite, and bentonite were measured by a commercial gas pycnometer using He, N2, and dry air. The ρs of 30 of the soil samples, glass beads, and crushed rock were also determined with a water pycnometer. The ρs of 36 soil samples determined by He and 30 samples determined by water had narrow ranges with averages of 2.65 and 2.59 g cm −3, respectively. The ρs determined by air and N2 had much wider ranges with averages of 2.93 and 2.97 g cm −3, respectively. There was a near 1:1 relationship between ρs of all samples determined by air and N2 with a highly significant ( p < .001) correlation coefficient ( r = .99). The average ratio of ρs determined by He and water was 1.03, but the correlation coefficient for their relationship was only .416. Although the relationship between ρs determined by He and either air or N2 was relatively strong ( r < .61), the regression coefficient was <.17. There was a strong relationship between soil clay content and ρs determined by N2 or air but a weaker, yet statistically significant ( p < .05) relationship when using He. Core Ideas: Average particle density of soils belonging to 12 textural classes determined by helium was 2.65 g cm −3 . Average particle density measured by air and nitrogen were 2.93 and 2.97 g cm ‐3, respectively. Helium, nitrogen, or air can be used to measure particle density of coarse‐textured soils. Only helium should be used to measure particle density of medium‐ and fine‐textured soils.